Black manhood in Richard Wright’s Native Son and James Baldwin’s If Beale Street Could Talk: racial criminalization, death, and the myth of the black rapist - Isadora Martins Amaral Castro (2023)
This thesis examines the fictional representations of black manhood in the novels Native Son by Richard Wright and If Beale Street Could Talk by James Baldwin. Guided by the premise that black men have historically experienced unique and distinct forms of oppression in the United States, which give rise to a particular form of vulnerability, the work analyzes how Wright’s and Baldwin’s selected works engage with the themes of racial criminalization, subjectivity, death, and the so-called “myth of the black rapist,” a cultural narrative that has been used to justify various forms of violence against black men since the 19th century. The investigation begins with a review of the historical processes linked to the anti-black punitive tradition that has permeated American society since its colonial origins and ultimately developed into contemporary mass incarceration. Discussions related to black manhood and death in the novels are then offered, adopting the perspective of African-American philosopher Tommy J. Curry, particularly his theoretical framework outlined in The Man-Not: Race, Class, Genre, and the Dilemmas of Black Manhood. The notions of Black male vulnerability and Black male death, as interpreted through Curry’s work, serve as guiding principles for the proposed readings. Lastly, this thesis explores the myth of the black rapist and examines sexual violence and sexual vulnerability in the selected literary works. In parallel, the commonalities and divergences between the novels are observed throughout the work, oriented by the argument that If Beale Street Could Talk can be seen as a response to Native Son, with Baldwin engaging in a revision of the aspects he deems problematic in Wright’s novel.